MEMAKNAI IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY MENUJU SUSTAINABILITY DALAM PERSPEKTIF SOCIAL PRACTICE BOURDIEU - Rochayatun, Sulis (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2021)
This study aims to interpret the implementation of CSR in achieving corporate sustainability studied with Bourdieu's social practice theory. This study uses an interpretive paradigm with a phenomenological approach. The research location is PT. Tirta Investama - Pasuruan Keboncandi Factory. Data collection was carried out by conducting in-depth interviews with key Â informants who took turns to obtain data triangulation.The results showed that the implementation of CSR on the research site was well organized and structured and became a permanent and incidental program. CSR is implemented based on the principle of "dual commitment", which is the belief that if a company wants to be successful in business, the company must be successful socially. The process of defining and understanding CSR towards corporate sustainability is pursued by forming a habitus, maintaining the existence of capital and mastering the field, this is in line with Bourdieu's concept of social practice.